“The Fantastic Binomio” strategy and the production of texts - Salinas Infantes, Magali J. (2024)
On the basis of the logic of scientific research, the central objective of the research was determined, as follows: Demonstrate the influence index of the strategy "The Fantastic Binomial" in the development of the production of texts, in primary school students from the Educational Institution No. 32223, "Mariano Dámaso Beraún" of Amarilis, Huánuco, period 2021. To achieve this purpose, two methods were used: observation and experimental. The first made it easier to determine the problem issue and the second to apply the independent variable in order to improve the dependent variable. Continuing with this line, the type of research was established, considering the nature of the research, the applied one was prioritized. The reason, the problem needed a factual solution, under these parameters, with the design and implementation "The Fantastic Binomial" in the development of the production of texts for regular basic education students. Established the objective, methods and type of research, the following results were reached: PROOF: 99.85%, students who DID significantly improve in the development of text production, in primary education students and DISPROOF: 0.29%, students that did NOT improve their development of text production.